Representation of character education values based on Lickona’s perspective in english textbook at Indonesian elementary school - Banun Havifah Cahyo Khosiyono; Siti Rochmiyati; Imam Ghozali; Sulaimon Jamiu Temitope; Muhamad Fajarudin; Aziz Murof Suharyanto (TAMANSISWA INTERNATIONAL JOURNAL IN EDUCATION AND SCIENCE, 2022)
The context of this study is the Society 5.0 period in the field of education. Children’s education begins in elementary school. All human potential must be developed via education if people are to develop into people who can uphold moral principles. As a result, the Indonesian government is creating primary school textbooks that may include moral principles in the teaching and learning process. This research looked at character education from Lickona's perspective in English textbooks at the 4th grAde Indonesian Elementary school. Descriptive qualitative research of this kind includes steps of data gathering, data reduction, data presentation, and conclusion-making. The result shows that English Textbooks for Fourth Grade Elementary School Students Curriculum Merdeka apply characters based on Lickona's perspective from all aspects, although not every chapter has each character aspect based on Lickona's perspective.